2015
DOI: 10.1542/peds.2014-0898
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Neurodevelopmental Outcome in Extremely Preterm Infants

Abstract: BACKGROUND: Extremely preterm infants are at risk for neurodevelopmental impairment (NDI). Early cranial ultrasound (CUS) is usual practice, but near-term brain MRI has been reported to better predict outcomes. We prospectively evaluated MRI white matter abnormality (WMA) and cerebellar lesions, and serial CUS adverse findings as predictors of outcomes at 18 to 22 months' corrected age.METHODS: Early and late CUS, and brain MRI were read by masked central readers, in a large cohort (n = 480) of infants ,28 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
164
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 217 publications
(179 citation statements)
references
References 40 publications
(20 reference statements)
5
164
1
7
Order By: Relevance
“…First, CUS examinations in ELGANs should routinely include a mastoid view for visualization of the cerebellum; this view was included in less than half of the CUS scans performed in the current study. In Hintz et al 6 Lastly, in the current study a substantial proportion of surviving infants with severe abnormalities on either late CUS or MRI scans were only mildly impaired or unimpaired at 18 to 22 months (26.9% and 16.7%, respectively). These findings point out the perils of prediction for individual infants and our poor understanding of the impact of social or other factors on brain development.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…First, CUS examinations in ELGANs should routinely include a mastoid view for visualization of the cerebellum; this view was included in less than half of the CUS scans performed in the current study. In Hintz et al 6 Lastly, in the current study a substantial proportion of surviving infants with severe abnormalities on either late CUS or MRI scans were only mildly impaired or unimpaired at 18 to 22 months (26.9% and 16.7%, respectively). These findings point out the perils of prediction for individual infants and our poor understanding of the impact of social or other factors on brain development.…”
supporting
confidence: 46%
“…[2][3][4] This observation has led to recommendations that a routine brain MRI examination at term postmenstrual age be performed for all extremely low gestational age newborns (ELGAN) as a way to better predict the risk for NDI. 5 In this issue of Pediatrics, Hintz et al 6 describe the first large prospective evaluation of early (4-14 days) and near-term (35-42 weeks postmenstrual age) CUS and near-term brain MRI scans in the prediction of NDI at 18 to 22 months. In a prospective cohort of 480 infants born at ,28 weeks' gestation who underwent all 3 scans, the primary outcome of NDI or death was assessed by certified examiners.…”
mentioning
confidence: 99%
“…However, our study differs from those that have found associations of WM injury on near-term MRI with cognitive outcomes. Moderate-to-severe WM injury on structural MRI was a predictor of NDI in several relatively large cohorts[6, 810]. Woodward et al[9] studied 167 very preterm infants and observed that moderate-to-severe WM abnormality predicted severe cognitive delay, severe motor delay, CP, neurosensory impairment, and NDI at 2 years corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, brain MRI has become increasingly utilized in this population. Early evidence with conventional MRI at term-equivalent age (TEA) suggests that MRI may improve prognostication and identification of those at highest risk for impairments when compared to cranial ultrasound[4, 610]. Yet, more objective and accurate models for predicting NDI, especially cognitive outcomes, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…It accounts for 10% of the cerebral palsy cases and 25–50% of cognitive/behavioral deficits observed in VLBW preterm survivors [1]. Hintz et al [2] reported that 19.3 % of the surviving preterm infants developed cerebellar lesions. The pathogenesis of WMD primarily involves cerebral hypoxia-ischemia (HI) injury, systemic inflammation, and maternal or fetal infection.…”
Section: Introductionmentioning
confidence: 99%